2007
DOI: 10.1002/biof.5520310102
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic potential of Citrus sinensis and Punica granatum peel extracts in alloxan treated male mice

Abstract: An investigation on the effects of four different concentrations of peel extract from Citrus sinensis (CS) or Punica granatum (PG) in male mice revealed the maximum glucose lowering and antiperoxidative activities at 25 mg/kg of CS and 200 mg/kg of PG. In a separate experiment their potential was evaluated with respect to the regulation of alloxan induced diabetes mellitus. While a single dose of alloxan (120 mg/kg) increased the serum levels of glucose and alpha-amylase activity, rate of water consumption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 30 publications
6
55
0
Order By: Relevance
“…Cyclic monoterpene, DL-limonene [218]. Ascorbic acid [219] Maximum glucose lowering and antiperoxidative activities in alloxan diabetic mice [220]. Antithyroidal, hypoglycemic, and insulin stimulatory properties, suggesting its potential to ameliorate both hyperthyroidism and diabetes mellitus [221].…”
mentioning
confidence: 99%
“…Cyclic monoterpene, DL-limonene [218]. Ascorbic acid [219] Maximum glucose lowering and antiperoxidative activities in alloxan diabetic mice [220]. Antithyroidal, hypoglycemic, and insulin stimulatory properties, suggesting its potential to ameliorate both hyperthyroidism and diabetes mellitus [221].…”
mentioning
confidence: 99%
“…In a separate experiment their potential was evaluated with respect to the regulation of alloxan induced diabetes mellitus. While a single dose of alloxan (120 mg/kg) increased the serum levels of glucose and alpha-amylase activity, rate of water consumption and lipid peroxidation (LPO) in hepatic, cardiac and renal tissues with a parallel decrease in serum insulin level, administration of 25 mg/kg of CS was found to normalize all the adverse changes induced by alloxan, revealing the antidiabetic and anti peroxidative potential of tested fruit peel extracts [59].…”
Section: Citrus Speciesmentioning
confidence: 99%
“…Recently, a lot of researches have been done concerning the bioactivities citrus byproducts. Results have shown that citrus extract exerted many bioactivities including anticancer (Visalli et al, 2014), antioxidant, analgesic, anti-inflammatory (Sood et al, 2009), antiulcer (Bhavitavya et al, 2012), hepatoprotective (Abirami et al, 2015), cardioprotective (Campelo et al, 2011), anxiolytic (Carvalho-Freitas and Costa, 2002), antiviral (Balestrieri et al, 2011), anti-microbial (Shende et al, 2015) antiobesity (Cardile et al, 2015) and antidiabetic activity (Parmar and Kar, 2007). These actions were correlated to the wide variety of secondary metabolites produced by citrus including polyphenolic compounds, alkaloids, limonoids, pectins and dietary vitamin C (Benavente- Garcia and Castillo, 2008;Marti et al, 2009;Murakami et al, 1997;Silalahi, 2002;Tundis et al, 2014;Visalli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%